GIS Application of Restaurant Location Mapping using Google Maps API - Yosef Umbu Robaka; Cecilia Dai Payon Binti Gabriel; Mitra Pertama Ayu (International Forum of Researchers and Lecturers, 2024)
A geographic information system are highly valuable tools that help individuals or visitors explore noteworthy destinations. Implementing GIS for online restaurant searches within Southwest Sumba Regency aims to assist users in effortlessly obtaining detailed and accurate information about restaurant locations, enabling them to identify and reach these spots efficiently. The purpose of this project is to design a GIS application that leverages the capabilities of the Google Maps API. This API represents a sophisticated set of modern programming tools that facilitate seamless interaction between different software systems. The GIS application is developed using the waterfall methodology, which emphasizes a structured software development lifecycle to ensure uniformity and operational clarity. Therefore, the results of this study, with a geographic information system mapping the location of eating restaurants can provide information to tourists, as well as the community regarding the location of eating restaurants in the Southwest Sumba Regency area quickly and easily.